Cubefree sum

n is cubefree 1 n 2 = A B π C \large \sum _{n \text{ is cubefree}}\frac{1}{n^2}=\frac{A}{B\pi^C}

The equation above holds true for integers A , B A,B and C C . If A A and B B are coprime positive integers, find A + B + C A+B+C .


Inspiration .


The answer is 321.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Otto Bretscher
Apr 24, 2016

The Euler Product is p ( 1 + 1 p 2 + 1 p 4 ) = p 1 p 6 1 p 2 = ζ ( 2 ) ζ ( 6 ) = π 2 6 945 π 6 = 315 2 π 4 \prod_{p}\left(1+\frac{1}{p^2}+\frac{1}{p^4}\right)=\prod_{p}\frac{1-p^{-6}}{1-p^{-2}}=\frac{\zeta(2)}{\zeta(6)}=\frac{\pi^2}{6}\frac{945}{\pi^6}=\frac{315}{2\pi^4} and the answer is 321 \boxed{321}

Two small issues: The π B \pi^B should be π C \pi^C and A , B A,B need to be co-prime positive integers.

Moderator note:

Good representation of the product to express this cubefree sum.

I've edited it. Thanks!

Julian Poon - 5 years, 1 month ago
Arjen Vreugdenhil
Apr 28, 2016

Every positive integer n n can be written uniquely in the form n = p q 3 n = p\cdot q^3 with p p cube-free. This provides a one-to-one correspondence between N \mathbb N and ( N c f , N ) (\mathbb N_{cf}, \mathbb N) .

Therefore n N 1 n 2 = p N c f q N 1 ( p q 3 ) 2 = ( p N c f 1 p 2 ) ( q N 1 q 6 ) ; \sum_{n \in \mathbb N} \frac 1{n^2} =\sum_{p\in \mathbb N_{cf}}\sum_{q\in\mathbb N}\frac 1{(pq^3)^2} \\ = \left(\sum_{p\in \mathbb N_{cf}}\frac 1{p^2}\right)\ \left(\sum_{q\in\mathbb N}\frac 1{q^6}\right);

If the desired value is X X then clearly ζ ( 2 ) = X ζ ( 6 ) X = ζ ( 2 ) ζ ( 6 ) = π 2 / 6 π 6 / 945 = 315 2 π 4 . \zeta(2) = X\cdot \zeta(6)\ \ \ \therefore\ \ \ X = \frac{\zeta(2)}{\zeta(6)} = \frac{\pi^2/6}{\pi^6/945} = \frac{315}{2\pi^4}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...